Passive heating increases bench-pull power output in highly trained swimmers - McKenzie, M. R.; Hogarth, L. W.; McKean, M. R.; Doyle, D. P.; Burkett, B. J. (International Journal of Sports Physiology and Performance, 2023)
Purpose: Determine the effects of skin temperature change on bench-pull power following a passive warm-up intervention with highly trained swimmers using multiple heated clothing garments.